Factors associated with exclusive breastfeeding practices in western Bhutan - Hari Prasad Pokhrel; Patcharanee Pavadhgul; Suwat Srisorrachatr (Bhutan Health Journal, 2018)
Introduction: Breastfeeding is widely accepted in Bhutan but there are wide range of practices, some of which are not in accordance with the recommendations of WHO. In 2015 the prevalence of exclusive breastfeeding under six months of age, in western region was only 33.8% while the national rate was 51.4%. This study aimed to identify the factors associated with exclusive breastfeeding practices in western Bhutan.